Modernizing Learning Media: Educational Content Design Training Using the Canva and Flipbook Platforms - Hajar, St; Haswani, Haswani; Nurindah, Nurindah; Puttiri, Puttiri; Nasir, Nasir (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2025)
The development of digital technology has brought significant transformation in the world of education, requiring teachers to improve their abilities in innovative learning methods. This research focuses on training in using the Canva and Flipbook applications as tools in developing digital learning media. Initial observations show that many teachers still use conventional media due to limited time and knowledge in design. Through a workshop held on October 5 2024, 54 participants from various educational institutions were trained to develop digital educational content. The results of the training show an increase in teacher competence in using Canva's advanced features and techniques for creating digital interactive books using Flipbook. Participants successfully integrated multimedia elements into learning, creating a more interesting and interactive learning experience. This workshop also builds professional networks between students and teachers, and increases teacher motivation to continue developing their digital competencies. In conclusion, this activity succeeded in improving the quality of the teaching and learning process through more effective use of digital technology.